Estudo da estruturacromossômica de Astyanax bockmanni (Teleostei, Characiformes) em diferentes populações: enfoque em cromossomos B - Daniel, Sandro Natal [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Among the fish of the Neotropical region, we have the Characidae family whose genus Astyanax is the most common and diverse, with 141 species validated. Studies with several species of the group have shown a particular population dynamics, leading to the formation of genetically variable populations, besides the occurrence of B chromosomes, which in this genus exhibit intense polymorphisms. These chromosomes are classified as additional elements dispensable, and are present in plants, fungi and animals of varying frequencies and morphologies. So, six distinct populations of Astyanax bockmanni collected in the basins of the Tietê and Paranapanema were analyzed, beyond samples of the species A. fasciatus and A. paranae carriers of supernumerary chromosomes. The studies were based on classical cytogenetic techniques (Giemsa staining, impregnation with silver nitrate, and C-banding), and molecular (fluorescence in situ hybridization FISH and animal by means of 18S and 5S rRNA probes; genes for histones H1, H3, and transposable elements Rex1, Rex3 and Rex6). We also performed microdissection, amplification, marking and hybridization of a B-specific probe acrocentric B chromosome of A. bockmanni, named Babock. The results indicated that all specimens of A. bockmanni and A. paranae presented 2n=50 chromosomes. A. fasciatus showed 2n=46 chromosomes default. All karyotypes of the three species were made up of chromosomes metacentric, submetacentric, subtelocentric and acrocentric types. The species A. bockmanni (Alambari population) were observed B microchromosomes metacentric and acro Supernumerary, were acro and subtelocentric observed in the species A. fasciatus, and the metacentric B chromosomes in type A. paranae. The six populations of A. bockmanni showed differences in the constitutive heterochromatin and multiple NOR except the population Capivara river, which indicated a simple NOR system. Additionally, the 18S rRNA gene revealed ...

Dentre os peixes da região Neotropical, temos a família Characidae, cujo gênero Astyanax é o mais comum e diversificado, contando com 141 espécies validadas. Estudos com diversas espécies do grupo têm demonstrado um dinamismo populacional particular, que leva à formação de populações geneticamente muito variáveis, além da ocorrência de cromossomos B, que neste gênero apresentam intensos polimorfismos. Estes cromossomos são classificados como elementos adicionais e dispensáveis, e estão presentes em plantas, fungos e animais, de diferentes morfologias e frequência variada. Frente a isso, foram analisadas seis populações distintas de Astyanax bockmanni coletadas nas bacias do rio Tietê e Paranapanema, além de exemplares das espécies A. fasciatus e A. paranae portadores de cromossomos supranumerários. Os estudos se basearam em técnicas citogenéticas clássicas (coloração com Giemsa, impregnação com nitrato de Prata, e bandamento C) e moleculares (hibridação in situ fluorescente e Zoo-FISH, por meio de sondas de DNAr 5S e 18S; genes para as histonas H1, H3; e elementos transponíveis Rex1, Rex3 e Rex6). Também realizamos a microdissecção, amplificação, marcação e hibridação de uma sonda B-específica do cromossomo B acrocêntrico de A. bockmanni, nomeada Babock. Os resultados indicaram que todos os exemplares de A. bockmanni e A. paranae apresentaram de 2n=50 cromossomos. Já A. fasciatus evidenciou 2n=46 cromossomos padrão. Todos os cariótipos das três espécies foram constituídos de cromossomos dos tipos metacêntricos, submetacêntricos, subtelocêntricos e acrocêntricos. Na espécie A. bockmanni (população Alambari), foram observados microcromossomos B acro e metacêntricos. Supranumerários meta, acro e subtelocêntricos observados na espécie A. fasciatus, e cromossomos B do tipo metacêntricos em A. paranae. As seis populações de A. bockmanni apresentaram divergências da heterocromatina ...
Keywords: Astyanax (Peixe); Cromossomos - Polimorfismo; DNA; Citogenética animal; Teleosteos; Livestock Cytogenetics